2014
DOI: 10.1309/ajcp9wyexkol9yuv
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Analysis of Epstein-Barr Virus Viremia and Its Significance in the Evaluation of Organ Transplant Patients Suspected of Having Posttransplant Lymphoproliferative Disorders

Abstract: We believe that pattern analysis of EBV DNA quantitation results could lead to the early diagnosis and timely treatment of PTLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 17 publications
0
23
1
Order By: Relevance
“…The development of PTLD has previously been shown to correlate with EBV viremia. 6 In contrast, our patient did not have a detectable EBV viral load by PCR despite a positive EBV in situ hybridization study on biopsy. Negative EBV viral loads, in fact, are characteristic for EBV+ MCU.…”
contrasting
confidence: 69%
“…The development of PTLD has previously been shown to correlate with EBV viremia. 6 In contrast, our patient did not have a detectable EBV viral load by PCR despite a positive EBV in situ hybridization study on biopsy. Negative EBV viral loads, in fact, are characteristic for EBV+ MCU.…”
contrasting
confidence: 69%
“…These uncontrolled EBV-driven lymphoproliferations are the best examples of the critical role played by host immunity in controlling EBV infection. In the setting of 3 pediatric PTLD patient PBMC and plasma In-house quantitative PCR >1000 copies/10 5 PBMC and >500 copies/ml [64] 57 transplant patients Serum In-house real-time PCR >50,000 copies/ml high risk of PTLD [69] 1 pediatric PTLD patient Plasma In-house real-time PCR >200 copies/ml [70] 3 pediatric PTLD patient Serum In-house nested PCR >5000 copies/ml [52] 6 adults at PTLD diagnosis Whole blood In-house quantitative competitive PCR >1000 copies/ml [59] 264 pediatric transplant patients Whole blood In-house real-time PCR >30,000 copies/ml [60] 6 adults at PTLD diagnosis Whole blood In-house quantitative competitive PCR >2000 copies/ml [61] 2 pediatric PTLD patient Whole blood In-house semi-quantitative nested PCR >30,000 copies/ml [62] 53 transplant patients Whole blood In-house real-time PCR >100,000 copies/ml high risk of PTLD [63] 41 transplant patients Whole blood Commercially available real-time PCR >100,000 copies/ml high risk of PTLD a Peripheral blood mononuclear cells. iatrogenic immune suppression which characterizes transplant patients, EBV-infected lymphoid cells may proliferate and expand, thanks to the driving force of several EBV antigens expressed during latency, mainly LMP-1.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that PTLD is accompanied by a significant increase in EBV levels in peripheral blood mononuclear cells (PBMC) [50,[53][54][55][56][57][58] and in whole peripheral blood [59][60][61][62][63]. In particular, increased levels of EBV-DNA in serum or whole blood have been found to be predictive of PTLD onset in post-transplant patients [62][63][64]. Nevertheless, high EBV-DNA alone is not always predictive of impending PTLD [51,65,66].…”
Section: Mechanisms For Ebv-driven Ptldmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be seen in the increased risk of lymphoma in patients with inflammatory bowel disease on immunosuppression [23][24][25]. The incidence of post-transplant lymphoproliferative disorders has been shown to increase with EBV viral load [26]. EBV has also been detected in colorectal adenocarcinoma, suggesting it as a possible contributing factor [27][28].…”
Section: Discussionmentioning
confidence: 99%